The Implications of Al-Māwardī's Thoughts on Community Economy During the Covid-19 Pandemic - Santosa, Ali; Janwari, Yadi; Rusyana, Ayi Yunus (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2021)
The study in this paper departs from Islamic economic thought proposed by Imam Al-Māwardī. He is a well-known figure as an Islamic thinker who contributed a lot to the order of all fields of state and religion, especially in the economic field. The purpose of this study is to find out Al-Māwardī's thoughts on Islamic economics and its implications for dealing with the current Covid-19 outbreak. The research method used is descriptive qualitative about the concept of Islamic economic thought proposed by Al-Māwardī, whose data sources are obtained from his books. The results of the research obtained are Al-Māwardī's concept of thought regarding the development of Islamic economics related to the state and economic activities, taxation, and influential market mechanisms so that they can continue to be implicated in overcoming these contemporary problems, such as the Covid-19 pandemic. Keywords: Islamic economy, taxation, market mechanism, Covid-19   Abstrak Kajian pada tulisan ini berangkat dari pemikiran ekonomi Islam yang dikemukakan oleh Imam Al-Māwardī. Beliau merupakan sosok yang terkenal sebagai tokoh pemikir Islam yang banyak memberikan sumbangsi pada tatanan segala bidang kenegaraan dan agama terkhusus pada bidang ekonomi.  Tujuan penelitian ini untuk mengetahui pemikiran Al-Māwardī terhadap ekonomi Islam beserta implikasinya yang dihadapkan dengan masalah wabah covid-19 yang terjadi sekarang ini. Metode penelitian yang digunakan deskriptif kualitatif mengenai konsep pemikiran ekonomi Islam yang dikemukakan oleh Al-Māwardī, yang sumber datanya diperoleh dari kitab-kitab karangannya. Hasil penelitian yang diperoleh ialah konsep pemikiran Al-Māwardī mengenai perkembangan ekonomi Islam yang berkaitan dengan negara dan aktivitas ekonomi, perpajakan, dan mekanisme pasar yang berpengaruh hingga dapat terus diimplikasikan dalam mengatasi masalah kontemporer ini, seperti pandemi Covid-19. Kata Kunci: Ekonomi Islam, perpajakan, mekanisme pasar, Covid-19